2012
DOI: 10.1080/15459624.2011.639232
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Approach to Respirable Quartz Exposure Control in U.S. Coal Mines

Abstract: Occupational exposure to high levels of respirable quartz can result in respiratory and other diseases in humans. The Mine Safety and Health Adminstration (MSHA) regulates exposure to respirable quartz in coal mines indirectly through reductions in the respirable coal mine dust exposure limit based on the content of quartz in the airborne respirable dust. This reduction is implemented when the quartz content of airborne respirable dust exceeds 5% by weight. The intent of this dust standard reduction is to rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…While these alarming trends have not been fully explained, a number of causal factors have been suggested (e.g., see [14][15][16][17][18][19][20][21][22][23]), including exposure conditions and specific dust characteristics. , and includes all reported categories of CWP (i.e., severity categories 1, 2, and 3, and progressive massive fibrosis (PMF)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these alarming trends have not been fully explained, a number of causal factors have been suggested (e.g., see [14][15][16][17][18][19][20][21][22][23]), including exposure conditions and specific dust characteristics. , and includes all reported categories of CWP (i.e., severity categories 1, 2, and 3, and progressive massive fibrosis (PMF)).…”
Section: Introductionmentioning
confidence: 99%
“…The roof rock (e.g., sandstone) in many of these mines includes significant silica content, and so higher concentrations of crystalline silica (quartz) may be expected in dust [19,23]. Many mines in parts of central Appalachia are also relatively small and accordingly have small labor forces.…”
Section: Introductionmentioning
confidence: 99%
“…Underground coal mine operation has always proved to be a very dangerous and hazardous environment [1] due to the presence of coal dust, methane, and other toxic gases [2,3]. It has been reported that approximately 33.8% of deaths that happen in the mining sector are a consequence of coal dust or methane gas explosions.…”
Section: Introductionmentioning
confidence: 99%
“…(2) We propose the seamless integration of key technologies of information systems based on IoT and cloud services for underground mine informatics, in which a cloud server communicates with mobile devices. (3) We originally proposed a single "Mine Warning Index (MWI)" for an easy and quick assessment of mine safety.…”
Section: Introductionmentioning
confidence: 99%
“…In the U.S., silica can be found in the respirable dust of coal mines, metal mines, and sand and gravel operations (Joy, 2011; Watts et al , 2012; Cauda et al , 2013). In coal mines, the primary source of mineral dust is the top strata above the coal seam (Schatzel, 2009); in non-coal mines, silica is a component of the dust present throughout numerous mining processes (Cares et al , 1973; Cauda et al , 2013); and in the industrial sand mining sector, crystalline silica in the form of sand is the main product of the industry.…”
Section: Introductionmentioning
confidence: 99%